Physical and Organoleptic Quality of Culled Layers Chicken Meat Using Marinated Asam Kandis Fruits (Garcinia dioica Blume) - Patriani, Peni; Hesti Wahyuni, Tri (Indonesian Journal of Agricultural Research, 2020)
Asam Kandis is one of the fruits with a sour taste that is often used in the spice. Asam Kandis is very effective as a food flavoring such as in meat and fish. Culled layers meat usually has a rough texture, tough and not preferred because it has a rough tenderness, so it needs natural herbs to improve tenderness or maintain the physical. This study uses a completely randomized design with 4 treatments and 4 replications. The treatment in this study marinated culled layers chicken in Asam Kandis consisting of 4 levels: 0%, 5%, 10%, and 15%. Research aimed to improve the physical and organoleptic quality of culled layers of chicken meat using Asam Kandis. The results obtained physical and organoleptic quality in culled layers chicken meat, which includes pH, drip loss, and tenderness, significantly affect the marinated Asam Kandis. Water content and cooking losses do not affect the marination of Asam Kandis and are quite effective. Conclusion in this research Asam Kais has a quite good effect on improving the quality of culled layers of chicken meat. It is recommended marination using Asam Kandis with a level of 9% effective maintain the quality of culled layers meat.